Application of the polygonal form for products on the basis of wood and cement composites on the example of wood concrete - Goncharova M. A., Proskuryakova A. O., Lamov I. V., Matchenko N. A., Dedyaev G. S., Mirzabaev R. R. (Interactive science, 2017)
the article describes products from wood concrete with application of a polygonal form and the features of structure of wood concrete as well. The authors have noted positive moments of highly efficient Superplasticizer C-3 implementation in the technology of wood concrete mixture manufacture.
Keywords: арболит; древесно-цементный композит; арболитобетон; паз-гребень; «LEGO» блок; wood concrete; groove crest; wood and cement composite; «LEGO» block